Building a global taxonomy of wildlife offenses. Issue 6 (24th June 2021) - Pascual, Maria; Wingard, James; Bhatri, Naila; Rydannykh, Alyona; Phelps, Jacob
Abstract: Most countries have many pieces of legislation that govern biodiversity, including a range of criminal, administrative, and civil law provisions that state how wildlife must be legally used, managed, and protected. However, related debates in conservation, such as about enforcement, often overlook the details within national legislation that define which specific acts are illegal, the conditions under which laws apply, and how they are sanctioned. Based on a review of 90 wildlife laws in 8 high‐biodiversity countries with different legal systems, we developed a taxonomy that describes all types of wildlife offenses in those countries. The 511 offenses are organized into a hierarchical taxonomy that scholars and practitioners can use to help conduct legal analyses. This is significant amidst competing calls to strengthen, deregulate, and reform wildlife legislation, particularly in response to fears over zoonotic threats and large‐scale biodiversity loss. It can be used to provide more nuance legal analyses and facilitate like‐for‐like comparisons across countries, informing processes to redraft conservation laws, review deregulation efforts, close loopholes, and harmonize legislation across jurisdictions. We applied the taxonomy in a comparison of sanctions in 8 countries for hunting a protected species. We found not only huge ranges in fines (US0 to 200, 000) and imprisonment terms (1.5 years to life imprisonment), but also fundamentally different approaches to designing sanctions for wildlife offenses. The taxonomy also illustrates how future legal taxonomies can be developed for other environmental issues (e.g., invasive species, protected areas). Abstract : Article impact statement : The taxonomy of wildlife offenses facilitates legal analyses, including thecomparison of offenses across jurisdictions. Abstract : Creación de una Taxonomía Mundial de Ofensas a la Fauna Resumen: La mayoría de los países tienen muchos instrumentos de legislación que gobiernan la biodiversidad, incluyendo una gama de disposiciones de leyes criminales, administrativas y civiles que declaran cómo se debe usar, manejar y proteger legalmente a la fauna. Sin embargo, los debates relacionados a la conservación, como el cumplimiento de las leyes, generalmente ignoran los detalles dentro de la legislación nacional que definen cuáles actos específicos son ilegales, las condiciones bajo las cuales aplican las leyes y cómo son sancionadas. Con base en una revisión de 90 leyes relacionadas con la fauna en ocho países con una gran biodiversidad y diferentes sistemas legales, desarrollamos una taxonomía que describe todos los tipos de ofensas a la fauna en aquellos países. Las 511 ofensas están organizadas en una taxonomía jerárquica que los académicos y los practicantes pueden usar para ayudar a realizar análisis legales. Lo anterior es significativo en medio de las peticiones competitivas por fortalecer, desregular y reformar la legislación de la fauna, particularmente como respuesta al miedo por las amenazas zoonóticas y la pérdida a gran escala de la biodiversidad. La taxonomía puede usarse para proporcionar análisis legales más matizados y para facilitar las comparaciones igual‐por‐igual entre los países, informar los procesos para reformular las leyes de conservación, revisar los esfuerzos por desregular, cerrar los vacíos legales y armonizar la legislación entre las jurisdicciones. Aplicamos la taxonomía en una comparación de las sanciones aplicadas en ocho países a la caza de especies protegidas. Encontramos no sólo una gama enorme de multas (de US0 a 200, 000) y términos de encarcelamiento (de 1.5 años a sentencias de por vida), sino también estrategias fundamentalmente diferentes para el diseño de las sanciones para las ofensas a la fauna. La taxonomía también ilustra cómo pueden desarrollarse las siguientes taxonomías legales para otros temas ambientales (p. ej.: especies invasoras, áreas protegidas).